Ethical issues in the occupation of Haiti : the case of morality by consensus. - SOUFFRANT, Eddy (1996)
Claims that despite the reality, international intervention in Haiti was morally repugnant. Argues that the policies of intervention are at best unjustifiable, and at worst a continuation of the colonialism of the nineteenth century.